CODESRIA Bulletin Online, No. 24, October 2021 - Freedom Mazwi in Conversation with Issa Shivji on the Peasantry, Neoliberalism and Alternatives - Shivji, Issa G.; Mazwi, Freedom (CODESRIA Bulletin, 2021)
Freedom Mazwi (FM): Good Morning. Welcome to this conversation with Mwalimu Professor Issa Shivji, a development and law expert. He has worked quite a lot in Africa, in places that include the University of Dar es Salaam, Zimbabwe and South Africa. He is one of the leading lights at CODESRIA, among the leading research institutions in Africa. Welcome Professor. Issa Shivji (IS): Thank you, Freedom. It is a pleasure to have this conversation. I am very much looking forward to it because such platforms allow us necessary freedom to explore very pertinent ideas more informally and more deeply. So, thank you Freedom for organising this. FM: Thank you Professor. The theme of our conversation today is the ‘Peasantry, Neoliberalism and Alternatives.’ As we might be aware, the peasantry is under massive attack not only in Africa but the global South broadly. This is why we considered this to be an important conversation. We will discuss the peasantry and its challenges, with extended consideration of what the alternatives may be. Let me start by asking you to define the peasantry. We know that it is a debated concept. There are various views on the peasantry, its characteristics and why is it important. IS: Thank you Freedom. I think you have raised a very important issue. I would like to briefly start with the traditional Marxist take on the peasantry. Karl Marx himself, based on the European experience, thought that with the development of capitalism, the peasant – basically meaning the smallholder who survives on land, produces on land – will disappear, and a large mass of people will become the industrial proletariat. It was in this regard that when it came to politics, we have Marx on record calling peasants a ‘sack of potatoes’ because he did not see a lot of potential in the peasantry for revolutionary change. Although that was based on the European experience, Marx did talk about countries of the South, particularly those in Africa. He however talked about them in relation to primitive accumulation of capital. But that was, for him, the original condition in developing his model of capitalism. Since then, we have had some theoretical and political developments. In this regard we must mention Rosa Luxemburg who disagreed with Marx. She argued that capitalist accumulation is not simply self-contained. Her position was that for capitalism to continue reproducing itself, it always needs noncapitalist sectors on which to feed for accumulation. She saw many of our countries as feeding capitalism through primitive accumulation. That was the initial argument during those debates. The second point that I think Rosa Luxemburg made, which is also very important for us, was that Marx’s formulae saw primitive accumulation as the original condition and once capitalism has developed, we get what is called capitalist accumulation. It is based on labour and capital. The former is exploited to produce the surplus value and part of that surplus value is accumulated for the second cycle of expanded reproduction. Rosa Luxembourg’s argument was that primitive accumulation does not actually come to an end with capitalist development, but rather continues because exploitation of the non-capitalist sector based on primitive accumulation is essential for capitalist reproduction. Subsequently we had other developments starting with Lenin, going on to Mao and so on. And contrary to the predictions of the earlier Marxists, the socialist revolution happened not in the centre but in the semi-periphery, i.e. Russia. Russia of the time still had pre-capitalist relations in the countryside and also a mass of peasantry. That is where Lenin politically located his thesis of worker–peasant alliance. Previously, the peasantry had been seen as a conservative force but for Lenin, the working class could rely on the peasantry and lead the peasantry for revolutionary transformations and changes. This thesis was developed much more in the periphery, particularly in China. The Chinese argument about the role of the peasantry makes a very important contribution to Marxist theory and politics. It has been pretty prominent in discussions of Marxism in many countries of the global South. But Mao still worked within the Marxist paradigm, and we should not forget that, initially at least, he saw the revolution happening in stages. First the national democratic revolution and then the socialist revolution. Later on, Mao developed a thesis of some kind of continuous revolution thus more or less abandoning the stageist thesis. That is where I will end my introductory remarks. Now let me come to the question you raised in the context of the debates in the South. More recently, I would say in the last two or three decades, we have developed a thesis in the South, particularly in Africa, that exploitation by and accumulation of capital, which is dominated by the capital from the centre, is primarily based on the extraction of surplus from the peasantry. The dominant producers of surplus are the peasantry. As a matter of fact, the history of capital destroying the peasantry by turning them into a proletariat has to be modified when applied to many countries in Africa. Here, capital preserves the peasant form – the form of petty commodity production – but integrates it in the web of world-wide capital circuits. The dominant form of accumulation is primitive accumulation in which the peasant producer cedes to capital a part of his/her necessary consumption. Within this context, exploitation cuts into the producer’s necessary consumption. In effect, therefore, labour subsidises capital by taking on the burden of reproduction. This thesis has increasingly been debated among African intellectuals and more recently within our own Agrarian South Network (ASN). Dramatically, this has proven to be so under neoliberalism. My argument has been that many of the efforts that were made by independent governments essentially tried to move away from the dominant tendency of primitive accumulation of the colonial period. This was for the purposes of attempting to install some kind of capitalist accumulation by, for instance, abolishing migrant labour, raising wages and initiating some social services like education, health etc. This contributed to social wage and the adoption of some or other form of industrialisation, albeit in many cases, import substitution industrialisation. This was justified, rationalised and presented in a variety of nationalist and developmental ideologies. Regardless of what these countries called themselves, capitalist or socialist, the underlying driving force of their policies was to move away from primitive accumulation as the dominant tendency of accumulation. This was done to try and install some kind of expanded reproduction of capitalist accumulation. That project of capitalist development in the image of the historical European development, for various reasons which I am not going to get into, did not succeed. It failed. And neoliberalism, through which imperialism has now assumed an offensive, in my view, has brought back primitive accumulation as the dominant tendency. It is not the same kind of primitive accumulation that we have witnessed classically like, for example, the tendency of evicting the peasantry from land, although that too exists. There are now new forms of primitive accumulation which I think we need to reckon with. Before I proceed, you asked me the question of how we define the peasantry. For me, when we say the peasantry, I am thinking of smallholder producers on land. This includes not only those who cultivate and produce crops but also pastoralists. I will include them because very often we forget that pastoralists are a section of small producers on land. Pastoralists and the peasantry, directly or indirectly, derive their subsistence and incomes from land. That is where the centre of the agrarian question lies. Now having defined it so, a number of our scholars and intellectuals have tried to understand small producers within the specific political economy of our concrete situations. I also wrote an article in the 1980s arguing that capital, in this case monopoly capital, does not only destroy the so-called pre-capitalist relations but also preserves them. The so-called pre-capitalist sector is in essence capitalist in the sense that it is integrated in the world-wide accumulation of capital. For this reason, the so called pre-capitalist is only that in form. Under neoliberalism, we are witnessing new forms of primitive accumulation that include the privatisation and commodification of the commons. This also includes privatisation and commodification of public goods such as education, water, health, energy, finance etc. In essence, this is an attack on the production of public goods whose production was not subjected wholly to the market. That does not mean that the classical type of primitive accumulation, such as enclosures, has not continued. More recently we have witnessed, for example, a new wave of land grabbing. An important point to keep in mind is that when the land grabs occur, the smallholders who are thrown off the land do not become the proletariat since the expansion of industrial production and manufacturing is not happening. What happens is that they become landless and unemployed slum dwellers in the ghettos, as well as street hawkers and vendors. Large numbers of our youth between the ages of fourteen and twenty-five buy goods from merchants and hawk them in African cities and towns. They practically subsidise merchant capital and thus are subjected to a kind of primitive accumulation. In the countryside, the peasant is exploited. Based on this, I developed the thesis that the peasant is subjected to primitive accumulation in that the peasant producer cedes part of the necessary consumption to capital. Consequently, capital is subsidised because the reproduction of a peasant household/family is on the shoulders of the peasant household itself, largely women and children. The peasant, therefore, does not only produce surplus for capital, but also reproduces the peasant household by cutting into its own consumption and exerting super-human labour to be able to live sub-human lives. These are the processes which have intensified under neoliberalism. You will notice that all the programmes of land or agricultural reform put forward are meant to further entangle and integrate peasant production in the capitalist circuits and therefore reproduce the exploitative relationship I have talked about. Now coming to politics, in our ASN and the Sam Moyo African Institute for Agrarian Studies (SMAIAS) summer schools, we have argued that peasants, instead of being characterised as backward, have the potential to play a central role in revolutionary transformation. Several books produced by the ASN on social and peasant movements have shown recurrent struggles of the peasantry for land and livelihoods. Politically, in recent times, there has been a big shift on the issue of revolutionary agency. That is one tendency. There is another tendency which actually talks about de-peasantisation; that in the so-called South, particularly in Africa, the peasantry is disappearing. I think Deborah Bryceson, among others, subscribes to this position. We also find this view in Henry Bernstein, in a more nuanced form. There has been a debate based on these two tendencies – the tendency showing peasant potential and even advocating a kind of repeasantisation and the tendency to belittle the peasantry as a transformative force, a social category which is in fact disappearing – and that is where we stand. The debate continues. If you were to ask my opinion, using the Marxist method, the way Marx derived the revolutionary potential of the working class, similarly my analysis of the current financial capitalism which manifests itself as neoliberalism, I think we can derive the revolutionary potential of the peasant, small producers, small entrepreneurs, street hawkers and a whole group of people including those sometimes known as the lower-middle class. And I have tried to amalgamate these groups in the concept of ‘The Working People.’ Therefore, the agency of transformation is ‘The Working People.’ This has a different political nuance than the traditional ‘working class’ (proletariat) concept but is derived using the same method of Marxism. Of course, the concept of the ‘working people’ is still in its putative form and sounds somewhat abstract. We have to do a concrete analysis of each of our social formations and see what social classes and groups in our societies have a revolutionary potential of transforming our societies away from capitalism. Such analysis and empirical study should help us theorise the concept of ‘working people’ in a more rigorous fashion. On developing the so-called alternatives, my position has been that you cannot develop alternatives in the abstract. The life struggles of the working people in our countries are a school from which we can learn, theorise and develop the so-called alternatives. In the interim period, Samir Amin, for example, has argued for a national popular sovereign project. That is a kind of transitional analysis that allows you to make certain demands of the existing state, while recognising its limitations. The longer-term period of transformation, however, argues for a socialist transformation of the capitalist system. That is where we stand as far as intellectual debates are concerned. Meanwhile, real life situations and the struggles of the working people continue. ASN and SMAIAS generally have been at the forefront of producing empirical studies to show the forms of struggles of the working people in our various countries. I think I will end there as far as the first question is concerned. Let us develop the conversation further, Freedom. FM: Indeed many scholars like you, Samir Amin and Paris Yeros have taken the capitalist crisis into consideration and have indicated that we have reached a point where we can take this struggle from capitalism and progress towards a socialist future. In your view, what would it take to reach that socialist stage, and how many decades would it take? What should progressive activists do to ensure that we achieve that? IS: I think that is an interesting question. This is a kind of question you are frequently asked. When you give a response about socialism as a possible alternative, you are immediately confronted with a follow-up rhetorical question – where has socialism ever succeeded? All the countries which tried socialism failed. The problem is that our interrogators cannot even imagine what Samir Amin called the Long Road to Socialism. When we are talking about socialism, we are talking about an epochal change. We are not talking about years and decades because we are talking about overthrowing a system that has lasted for five centuries. So, to answer the second question about the failure of socialism, I would say this. The socialist revolutions that took place in countries like Russia, China, Cuba, Vietnam etc. were what one might call ‘revolutionary advances’. No doubt, these countries did make revolutionary advances. That is undeniable. These however, were only glimpses into the socialist future, not fully-fledged socialist societies. The fact that these advances failed in the countries that we described as socialist is nothing new in human history. Take the analogy of the development of capitalism, and the transition from various precapitalist modes of production – like feudalism and other forms of tributary systems – to capitalism. Those places like Venice and Portugal etc. in which capitalism first appeared are not the countries where capitalism ultimately succeeded. It succeeded in Britain. So, long transitions with a zig-zag trajectory, from one epoch to another, are nothing new in human history. Compared to the development of capitalism, revolutionary socialist advances had a shorter period. The Soviet Union lasted for only seventy years. China, from which we can derive lessons, despite many internal changes and struggles that have taken place, cannot be fully described as capitalist. The jury is still out. We have seen a small country like Cuba surviving all these years, despite the ups and downs. We have also seen initiatives taken in Venezuela, as well as initiatives of major land reforms in countries like Zimbabwe, etc. We have also seen bitter struggles in South Africa on the question of land which remains unresolved, yet it was a central question of the liberation movements. Based on these examples, I would say the era of revolutionary advances and struggles towards socialism is not over. It will, of course, take long, not just decades, yet we are witnessing major shifts and changes in the world. Those who predicted the end of history, and that capitalism was here to stay, have been proven woefully wrong. Capitalism is in deep crisis. Its very mode of existence is wars – from one war to another. Increasingly, and for the first time since the post-war period of the golden age of capitalism, people in both the South and the North are openly using the ideas and slogans of socialism, even though different people mean different things by socialism. Why not? Let hundred socialist flowers bloom! The second point I would like to make in this regard is that in the last ten to fifteen years we have witnessed major crises of capitalism. Neoliberalism, for example, which made its entry in the 1970s, and became politically significant in the 1980s, is already discredited. Its triumphalism has whittled down. It is almost in its last lag of existence. For how long did neoliberalism last, thirty years? We then witnessed a major crisis in 2008, which of course, took different forms in different countries. The crisis is not only economic. It is also a political one of political legitimacy in both the North and the South. One of the backlashes to neoliberalism is right-wing in the form of fascist tendencies that have been witnessed in countries like Brazil, India and some countries in Africa. But that is one tendency. Broadly, there also is a progressive left tendency. Youth all over the world are exploring and revisiting socialist ideas and developing new forms of struggle like the ‘Occupy movement’ or the upsurge of the Black Lives Matter movement or the farmers’ movement in India. All in all, there are rays of hope all over. In Africa, we have progressive tendencies emerging. Our problem is that our progressive forces, particularly the Left, remain largely unorganised. Organisation is the foremost task before us. For many years we have been talking about World Social Forums at the international level and civil society organisations (CSOs) at the local level. The impact of the latter has been marginal at best, and diversionary at worst. Theoretically infected by the liberal virus, and socially constructed by the middle classes, CSOs have failed to make a breakthrough. They have failed to resonate with the hearts, minds and real-life struggles of the working people. How do you organise the working people and how do working people get organised themselves? What kind of alternatives do you pose, what demands do you make and what are the sites of mass politics, for politics are where the masses are? In my view, those are the burning issues before the African Left. More recently I have been arguing that one of the important demands of the working people that can be put forward, and around which the working masses could rally, is reclaiming the commons. And not only the commons as traditionally understood to mean land and its resources, but commons in a new sense. By the new commons, I mean strategic sectors of the economy like education, health, finance, energy. These should also be considered the commons. They should be taken out of the realm of the law of value, that is, the market. These are the commons which we must struggle to reclaim. Why am I putting this forward? It is because it will sound feasible and doable by the working people. Thinking of land and its resources as the commons, not subject to private ownership, would not be new to many societies in Africa. The concept of ownership of land was introduced by colonialism. I recently argued this point in a foreword of a book published by SMAIAS – so that would not be new. Secondly, arguing for health, education, water, finance and energy as commons not subject to private ownership, but essentially producing public goods, also cannot be considered new because privatisation of these sectors has caused devastation to the working people. It has polarised our societies into small classes of a few who are filthy rich, and large masses of the poor who cannot afford paid education, health, water, electricity, etc. This can be the basis of organising the working people and it could be a political demand to the existing states. That is where I think the struggle stands. As I said, this is only a suggestion which requires further discussion and theorising. It is only after theorising that we can develop ideologies based on those demands and also understand how we can then learn from the experiences of the people to mobilise and take the struggles forward. FM: Moving on to another question that is almost linked to the previous one on alternatives, I would like us to spotlight Tanzania’s Ujamaa, a collectivisation project that was implemented by Mwalimu Julius Nyerere. This project has been vilified by a number of people who have argued that they had previously expressed that socialising does not work and therefore had discouraged developments that take that kind of path. As someone who went through this experience and followed it closely, what would you say was the major undoing of Ujamaa?1 I still think at some point people can try to relook and redefine it to make it work, but that can only be after a process of analysing its pitfalls. Did it really fail, and if so, why? IS: That indeed is an important initiative that we should table and discuss further. You will remember, Freedom, that Agrarian South: Journal of Political Economy produced a special issue that looked at both a hundred years of the Russian revolution and fifty years of the Arusha Declaration. In the publication, we tried to revisit both issues. I would like to say, first and foremost, that Ujamaa was undoubtedly a very progressive initiative in Africa. Secondly, both in its conception and implementation, it was a nationalist project, not a socialist one. The architect of the project himself often said that for him nation-building was primary, socialism secondary. If I were to put it in some kind of Marxist language, in Ujamaa social emancipation and class emancipation were subordinated to national building, which in turn meant giving primacy to national unity. The Social Question was subordinated to the National Question. The (national) unity of all classes trumped (social) class struggles. And politically speaking, as we have argued in our biography2 of Mwalimu Nyerere, in Book 3, that partly explains the so-called undoing of Ujamaa, because it was not seen as a social question. The national question was privileged. Within Ujamaa and within the political class, we ended up accommodating all kinds of tendencies including rightist tendencies which had no interest whatsoever in Ujamaa, and even went as far as to sabotage it. When the crunch came, this proto-bourgeoisie turned against Ujamaa. That is the thesis of Book 3 of the biography. Of course, we can say a lot about the shortcomings at the policy level, referring to failures of implementation etc., but that discourse does not take us far. Inevitably, it becomes tautological. For example, although the Arusha Declaration talks a lot about workers and peasants as the movers of the project, the truth is it was a top-down project. The agency to carry out this project was the state bourgeoisie which developed on the heels of Ujamaa. Ironically, the Arusha Declaration ended up creating a new class in its wings, so to speak; a kind of bureaucratic state bourgeoisie. It was this class that was supposed to drive Ujamaa! Secondly, although we kept singing that agriculture was the backbone of our economy, we did not transform agriculture. It remained the same agriculture of peasants using the same age-old instruments and implements. It is also important to point out that the peasants continued to be exploited to the maximum and without any support going back to the farmers. This issue has been analysed in the context of the land question and the truth and reality is that we failed to transform agriculture and we failed to address the agrarian question. The peasant was sucked dry. You are right when you say there was a time when Ujamaa was very much demonised as a ‘titanic failure’ (to use the late Mazrui’s hyperbole). The truth is, like many other African countries, whether capitalist or socialist, Tanzania found itself in deep a crisis in the late 1970s to the 1980s. All these countries had to submit to the so-called Structural Adjustment Programs (SAPs) to survive. I will not get deeper into this because we all know what happened. What I can say is that the consequences of adopting SAPs and neoliberal policies are now being dramatically seen and felt, and people (not only the masses but the so-called educated classes too) are revisiting the Arusha Declaration with nostalgia. If you read the Arusha Declaration today, you will realise that it was a pretty revolutionary document during its time, in spite of what happened in its implementation. There is a lot to learn from it. FM: That is a very interesting point. In the interest of time, let us move to another important issue which you and many others have raised. When we started this conversation, we talked about how an imperialist system somewhat disadvantages the South. In your writings you have gone further and postulated that that the solution is to delink. May you please provide clarity on this concept of delinking because some might interpret it to mean that we should not have any links with the outside world. IS: Firstly, delinking does not mean that there should not be any relations. Not only that it is impossible, but it is even undesirable. Delinking means subjecting your policies to the logic of national development not to the logic of imperialist and capitalist development. That is what you are delinking from. Simply put, you may say the kind of decisions you make and the policies you implement are meant to subject your development to the internal logic and not that of world capitalism. That is the meaning of delinking. How you do it is a different matter. Is it possible to do it? Yes, it is possible to do it and that is a political question. It does not happen mechanistically but depends on how well the popular classes are organised and mobilised to sustain the project of delinking. To answer your question more specifically, it is important to keep in mind that in this debate and discourse, all of us who subscribe to the delinking project must emphasise and audaciously put forward that imperialism exists. It continues to dominate the world system. Secondly, anti-imperialist struggles are extremely important. The third question is – and that is where the debate is right now – does antiimperialist struggle mean that you privilege the National Question and subordinate the Social Question? Does it mean that you move in stages, first resolve the National Question and then proceed to the Social Question? Or does it mean that in the current conjuncture you must privilege the Social Question and subordinate to it the National Question? I would say that this is what we are currently debating and that is where we have differences. To all these three questions, we cannot have ready-made answers but it is important to identify the burning questions of the day. At the abstract level of theory, these are the three most important questions and they all have empirical and practical manifestations. We have historic experiences of national liberation struggles. We also have historic experiences of those countries that gained national liberation which was not sustained after independence. It was squandered and we once again became the surrogates of imperialism. We have the experiences of some emancipatory tendencies which were nipped in the bud. For example, Amícar Cabral did not see national liberation as a stage but rather, a continuous process. If I may paraphrase him, he said ‘as long as imperialism exists, independence can only mean the national liberation movement in power’. This is a very profound statement. What are its implications? Take the example of South Africa and the stageist theory of some of its proponents. On the other hand, we had someone like Chris Hani who had a different vision of South Africa. He was killed. Amílcar Cabral was killed. These were strategic killings. Let us not forget them because in such struggles, individuals do matter. While we know that individuals do not make history, they do matter and play a critical role in certain circumstances. The turn that history takes does depend on the role of individual leaders. If you examine, and that is what we need to do, our history of national liberation, you’ll find that at very strategic moments, strategic people who had a different view of liberation were bumped off. Cabral and Chris Hani are examples. Would these countries have taken a different path had they lived, one cannot say. There is a point of view which is arising now which totally rejects the ‘National Question.’ It views the National Question as the colonial question. That is also problematic. I do not think that the National Question has exhausted itself but I will go along the line that in our present state of the struggle and politics of the left, the National Question needs to be subordinated to the Social Question. If we do not do that, we are likely to be identified with right-wing nationalisms and that is problematic. Today in South Africa, for example, you cannot simply continue harping on the National Question. The question which is very much on the table is the social one. There are people who have argued that the South African moment is a very advanced one because it subordinated the National Question to democracy by being all-inclusive. The question is, did it? It never addressed the Social Question. Capital, ‘white-capital’, stayed with its privileges. In that situation, it is now important to discuss the Social Question and not simply stick to the National Question or pontificate on some woolly idea about all-inclusive democracy. So, the National Question exists, it has a role, yes, but where do we place it. Before we end Freedom, I would like to make a couple of remarks. First, I want to suggest, I am of course thinking aloud, that we need to shift away from some of the dominant vocabulary. Of course, we are all agreed that the dominant discourse is that of the capitalists. We need to shift away from it. But there is also an NGO vocabulary which many of us, unconsciously or unintentionally, tend to adopt. That too is problematic. Here I am opening up myself to criticism. Is the term ‘alternatives’, for example, not very much part of the NGO discourse? I ask because in Marxist ideology, we talk of a ‘new world view’. In this ideology we do not talk about alternatives but we talk about building a better world with a new world view. I know it sounds abstract and utopian but the world’s history was made by utopias. The second point I would like to make is this: maybe we cannot explore this a lot here, but it is relevant when we are discussing the land question. There is a lot of debate about private individual ownership versus communal ownership and many of us think that the latter is progressive. I would actually want to suggest that we should move away from the concept of ownership altogether. That is why I am trying to develop, and maybe we can debate it, the concept of the ‘commons’. The commons are not ‘communally owned’. They are only managed by the community through its democratic organs. Finally, there is the question of the classes which I would want to address to my fellow comrades from the Marxist tradition. Many of us think that radical political economy and the analysis of classes is a Marxist method. It is not. Marxism was a critique of political economy, not its affirmation. The concept of class was developed by the classical political economists before Marx. What was specific to Marxism was the concept of historical materialism and the central problematic of historical materialism is class struggle. The question of class struggle has been discarded in our discussions. I would therefore like to suggest that we need to dig deeper in our summer school, workshops and in our work to understand better the question of historical materialism because, if we disregard it, we open ourselves to a very common criticism that Marxists are reductionists who only talk about economics and not politics. We also become susceptible to the criticism that Marxists talk about the ‘rule of capital’ but not ‘how capital rules’. That is inaccurate but it is a critique that is at times addressed to us, and on many occasions justified. So, Freedom, that is all from me, unless you have another question you may wish to add. FM: Thank you so much Professor. We unfortunately have run out of time, but we can always find time and discuss other issues. There indeed are some issues which we need to discuss in depth even towards the summer school. These especially relate to land: private ownership versus communal ownership. I think we need to dig deeper into these issues, theorise and come up with some practical solution instead of always continuing with those binaries of privatisation and communal ownership. As history and experience have shown, communal ownership is not the solution and private ownership has some weaknesses as well. Other issues that you raised on Marxism and class also need to have time dedicated to them. I think for today we can end here. Thank you very much for joining us. IS: Thank you Freedom for this discussion. I hope it will stimulate further discussions. Notes Henceforth not Issa G. Shivji et al, (2020) Development as Rebellion: A Biography of Julius Nyerere, Dar es Salaam: Mkuki na Nyota.